2006
DOI: 10.1021/jp064452v
|View full text |Cite
|
Sign up to set email alerts
|

Ion Conduction Mechanisms and Thermal Properties of Hydrated and Anhydrous Phosphoric Acids Studied with 1H, 2H, and 31P NMR

Abstract: To understand the behaviors of phosphoric acids in fuel cells, the ion conduction mechanisms of phosphoric acids in condensed states without free water and in a monomer state with water were studied by measuring the ionic conductivity (sigma) using AC impedance, thermal properties, and self-diffusion coefficients (D) and spin-lattice relaxation times (T1) with multinuclear NMR. The self-diffusion coefficient of the protons (H+ or H3O+), H2O, and H located around the phosphate were always larger than the diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
52
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 24 publications
(51 reference statements)
11
52
0
Order By: Relevance
“…Thus this crossover in the temperature dependence of conductivity and τ σ provides another way to estimate Tg of our materials. Comparison of conductivities in deuterated and hydrogenated PAs (Fig.2c) reveals a strong isotope effect at all studied temperatures and compositions R. This result agrees with earlier studies [22] where a decrease of conductivity was reported in partially deuterated PAs, although these measurements were limited to high temperatures only. The observed strong isotope effect (Fig.2c) contradicts the vehicular mechanism for proton conductivity, for which no measurable isotope effect is expected due to very small changes of the mass of molecular units (vehicle) upon D/H substitution.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Thus this crossover in the temperature dependence of conductivity and τ σ provides another way to estimate Tg of our materials. Comparison of conductivities in deuterated and hydrogenated PAs (Fig.2c) reveals a strong isotope effect at all studied temperatures and compositions R. This result agrees with earlier studies [22] where a decrease of conductivity was reported in partially deuterated PAs, although these measurements were limited to high temperatures only. The observed strong isotope effect (Fig.2c) contradicts the vehicular mechanism for proton conductivity, for which no measurable isotope effect is expected due to very small changes of the mass of molecular units (vehicle) upon D/H substitution.…”
supporting
confidence: 91%
“…NMR studies of PA found that the average proton mobility is more than 4 times higher than phosphorus mobility, clearly indicating a proton transfer mechanism of conductivity [22]. Recent detailed analysis based on ab initio molecular dynamics studies [21] suggested that, indeed, proton transport in PA involves the intermolecular Grotthuss-like proton transfer mechanism.…”
mentioning
confidence: 99%
“…(2)). According to Chuang et al [34] a decrease of conductivity of orthophosphoric acid was observed on the formation of pyrophosphoric acid at higher temperatures [35]. The activation energy calculated from the regression lines of samples AP4 and AP5 are listed in Table 4.…”
Section: Impedance Spectroscopy and Conductivitymentioning
confidence: 94%
“…But even this mechanism leads to a proton conductivity of only approximately 0.1 S cm À1 just above the melting point, which actually increases through the addition of water to a maximum of about 0.3-0.5 S cm À1 . [17] The discussion of the conduction mechanism in the nanoassembly of trimesic acid and melamine by Ji and coworkers is by far not meeting todays understanding of proton-conduction phenomena, which is just adumbrated here. But since we did not want to exclude the possibility of an unexpected discovery, we prepared whiskers in the same way that Ji and co-workers did and measured the conductivity in humidified atmosphere.…”
Section: Angewandte Korrespondenzmentioning
confidence: 98%